The Great Preglacial “Bell River” of North America: Detrital Zircon Evidence for Oligocene–Miocene Fluvial Connections Between the Colorado Plateau and Labrador Sea - Sears, James W.; Beranek, Luke P. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2022)
The idea of a great pre-glacial river that drained much of North America into the Arctic waters of modern Canada was first suggested in 1895 by Robert A. Bell. In the 1970s, petroleum exploration in Hudson Strait and the Labrador Sea located the massive, submerged delta of what is now known as the Bell River. Reconstructions suggest that three main branches of the Bell River joined up near modern Hudson Bay. The eastern branch largely drained the Canadian Shield, but the central and western branches had headwaters in the Cordilleran orogenic belt and its foreland in the present-day U.S. and northwestern Canada, respectively.We present new detrital zircon U–Pb data from Lower Oligocene and Lower Miocene sand from an exploration well in the Saglek delta of the northern Labrador Sea. In conjunction with other detrital zircon results from the Labrador Sea (and elsewhere) these data record the configuration and history of this continental-scale drainage basin in more detail. Mesozoic and younger detrital zircon grains (< 250 Ma) are subordinate to Precambrian age groupings, but Cenozoic populations become more abundant during the Oligocene, suggesting that the basin had expanded into areas now occupied by the Colorado Plateau and the Basin-and-Range Province. Proterozoic and Phanerozoic detrital zircon grain populations in Saglek delta sediments are similar to those of the Pliocene Colorado River. The results support an earlier idea that initial incision of the Grand Canyon and denudation of the Colorado Plateau were associated with a north-flowing paleo-river that fed into the Bell River basin. This contribution continued until the Pliocene capture of this ancestral river by the Gulf of California basin, after which the excavation of the modern Grand Canyon was completed. The Bell River drainage basin was later blocked by the expansion of Pleistocene ice sheets.